Legacy Lead in Urban Garden Soils: Communicating Risk and Limiting Exposure - Paltseva, Anna A.; Cheng, Zhongqi; McBride, Murray; Deeb, Maha; Egendorf, Sara Perl; Groffman, Peter M. (Frontiers in Ecology and Evolution, 2022)
Lead (Pb) exposure has long been recognized as a hazard to human health. Urban garden soils often contain elevated levels of Pb, mainly from legacy sources, which is a main barrier for urban gardening. The capacity of gardeners to access, understand, and act on scientific data related to soil contamination is also variable. This synthesis paper briefly summarizes the current scientific knowledge on soil Pb in urban gardens. Our objective is to produce clear recommendations about assessing actual risks and limiting exposure. First, we synthesize the nature and extent of soil contamination with Pb, and then describe how the bioavailability and risk of this contamination to humans is assessed. We then go on to potential exposure pathway through plants and remediation methods to improve soil health and reduce human exposure. We have developed best management practices for practitioners that include: (1) urban soil testing should be prioritized because of the high probability of Pb contamination, and urban gardening should not begin until thorough testing or remediation has been done; (2) documentation of land-use history should be required in all property transactions so that the potential for soil (and other) contamination can be clearly identified; (3) amendments cannot be relied upon as a treatment for contaminated soils to reduce risk to gardeners because they do not always make contaminants less harmful; (4) certain crops (such as fruiting vegetables) are much less susceptible to contamination than others and thus should be prioritized in urban gardens; (5) wherever feasible, raised beds filled with upcycled local mineral and organic materials are the preferred substrate for urban gardening. Further monitoring of potentially contaminated and remediated soils as well as effective communication with the public are necessary to ensure human safety.